2016
DOI: 10.1016/j.jcin.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors, and Outcomes of Permanent Pacemaker Implantation Following Transcatheter Aortic Valve Replacement

Abstract: Early PPM implantation is a common complication following TAVR, and it is associated with higher mortality and a composite of mortality or heart failure admission at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
188
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(222 citation statements)
references
References 33 publications
26
188
7
1
Order By: Relevance
“…Firstly, the presence of a pre‐existing PPM could be a marker of increased patient risk. In fact, in studies reporting baseline characteristic of patients with and without pre‐existing PPM , subjects with permanent pacing before the procedure had higher rate of risk factors such as diabetes and prior myocardial infarction, lower left ventricular ejection fraction (EF) and higher EuroSCORE (Supporting Information Table 5). This might explain why this finding was mostly observed in patients undergoing trans‐apical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the presence of a pre‐existing PPM could be a marker of increased patient risk. In fact, in studies reporting baseline characteristic of patients with and without pre‐existing PPM , subjects with permanent pacing before the procedure had higher rate of risk factors such as diabetes and prior myocardial infarction, lower left ventricular ejection fraction (EF) and higher EuroSCORE (Supporting Information Table 5). This might explain why this finding was mostly observed in patients undergoing trans‐apical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The CoreValve high risk pivotal trial reported a PPM implantation rate of 19.8% in patients undergoing TAVR and 7.1% in patients undergoing SAVR ( P < 0.001) . Likewise, in a recent review of the Society of Thoracic Surgeons/American College of Cardiology TVT registry, the reported PPM implantation rate within 30‐days of TAVR was 6.7% with significantly more among those receiving self‐expanding valves (25.1%) versus balloon‐expanding valves (4.3%) .…”
Section: Discussionmentioning
confidence: 99%
“…22 These 1-year adverse outcomes were also seen by Fadahunsi and colleagues in an analysis of 9785 patients in the US Transcatheter Valve Therapy registry. 44 However, it is difficult to draw comparisons with the available data, given the different prostheses and periods in addition to the relatively short follow-up periods.…”
Section: Discussionmentioning
confidence: 99%